2015
DOI: 10.4067/s0718-95162015005000058
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of cowpea beans with iron: iron´s influence on mineral content and yield

Abstract: Iron (Fe) deficiency is the most prevalent nutrient deficiency worldwide. Agronomic biofortification is an agricultural strategy for improving the micronutrient concentrations in staple food plants. At present, fertilization is a major vehicle for changing plant mineral contents and food quality. A greenhouse study was conducted to assess the effects of iron chelate and ferrous sulfate applications on the biofortification of Fe and its impacts on the mineral content and yield of cowpea beans. Four application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
3
22
1
2
Order By: Relevance
“…Roosta et al (2015) reported that the highest As displayed in Table 5, the use of polymeric monodispers iron oxide nanoparticles at 0.25 g L -1 Fe content in the plant root could significantly increased by 48.85% (Table 5). The results were congruent with the study of Armin et al (2014) and Márquez-Quiroz et al (2015). In addition, the foliar use of this iron source resulted in increasing iron absorption of root from soil.…”
Section: Characterization Of Plantsupporting
confidence: 82%
See 1 more Smart Citation
“…Roosta et al (2015) reported that the highest As displayed in Table 5, the use of polymeric monodispers iron oxide nanoparticles at 0.25 g L -1 Fe content in the plant root could significantly increased by 48.85% (Table 5). The results were congruent with the study of Armin et al (2014) and Márquez-Quiroz et al (2015). In addition, the foliar use of this iron source resulted in increasing iron absorption of root from soil.…”
Section: Characterization Of Plantsupporting
confidence: 82%
“…As shown in Table 3 The results are consistent with the results of the previous studies (Márquez-Quiroz et al, 2015;Hernán-dez-Castro et al, 2015) in which fertilizing with iron sources could significantly improves the Fe concentration in cowpea plant. In the greenhouse experiment, it was reported that some of polymeric hydrated sources provides small environment within the root zone which keeps Iron sulfate available to plants compared with its non-polymeric use (Mikkelsen, 1994).…”
Section: Characterization Of Plantsupporting
confidence: 82%
“…Such difference, although it could be partially due to a difference in terms of growth cycle length between sprouts and microgreens, further highlights the importance of examining a larger variety of species to identify the ones that are more suitable to Fe biofortification. Differences in Fe content have been also reported between biofortified green and red pigmented lettuce leaves by Giordano et al and cowpea by Márquez-Quiroz et al, while other factors may also affect the biofortification efficiency including growing conditions and farming practices [28,41,79,80,87]. Considering that the RDA for Fe is estimated at 8-18 mg per day for adults older than 18 years old [14,77], the consumption of even small amounts of these three microgreens could help to cover the total daily requirements and they could be considered as useful dietary supplements, especially in the case of pregnant women where RDA of Fe increases to 27 mg per day.…”
Section: Microgreens Nutrient Accumulation Response To Iron (Fe) Enrimentioning
confidence: 66%
“…Fertilizer application is one of the agronomic approaches that can help to enhance the nutrition security through improving the quality of grains in addition to its role in increasing productivity (Pathak et al, 2012;Márquez-Quiroz et al, 2015). Soil zinc deficiency is common in most of the chickpea growing areas of the world (Khan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%